Metaphors in Children Narrative on Massive Open Online Courses for Millennials’ Elementary Schools Students During Covid-19 - Ferril Irham Muzaki (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
The Covid-19 pandemic opens opportunities for social media businesses, especially MOOCs to develop various kinds of products which in turn make learning easier for elementary school students, at the same time opening up new business fields for students who are pioneering careers in the field of information and communication technology. This study aims to (1) to describe moral messages that are packaged in metaphors in international children’s stories, (2) to analyze moral messages that are packaged in metaphors in international children’s stories, and (3) to encode the metaphors used in international children’s stories. This research uses theme analysis. The research data in this study are the form of phrases, clauses, and sentences that contain moral messages. The data source of this research is children’s stories on the internet. This research produces findings that metaphors used to package moral messages in children’s films consist of nine forms, namely 1) animal metaphors (2) everyday metaphors, and (3) situation metaphors. The conclusion of this study is the moral message for learning materials in elementary schools delivered in the form of children’s stories that are packaged in the form of metaphors.